Analysis of Clinical Characteristics and the Effect of Symptomatic Supportive Treatment for Severe Neonatal Enterovirus Infection - Xuan Z; Wang T; Li N; Tang Z (Infection and Drug Resistance, 2025)
Zhe Xuan,1 Ting Wang,1 Ning Li,1 Ziqian Tang2 1Department of Neonatology, Zhuzhou Central Hospital, Zhuzhou, Hunan, 412000, People’s Republic of China; 2Department of Obstetrics and Gynecology, Zhuzhou Central Hospital, Zhuzhou, Hunan, 412000, People’s Republic of ChinaCorrespondence: Ziqian Tang, Email qnzu370@163.comObjective: To retrospectively analyze cases of neonatal enterovirus (EV) infection, identify risk factors for severe infection, pathological characteristics, and prognostic differences, and provide a basis for early identification of high-risk neonates.Methods: Neonates diagnosed with EV infection and admitted to Zhuzhou Central Hospital between January 2020 and December 2023 were included in the study. Based on disease severity, they were divided into a mild infection group (n = 149) and a severe infection group (n = 44). Data on demographic characteristics, clinical manifestations, laboratory findings, treatment methods, and prognosis were collected and statistically analyzed using SPSS 26.0.Results: Compared to the mild infection group, the severe infection group had lower gestational age (36.61 vs 38.50 weeks, P < 0.001) and higher preterm birth rates (P < 0.05). They presented earlier with higher incidences of rash, respiratory symptoms, and sepsis-like signs (all P < 0.05). Severe cases had significantly higher rates of pneumonia, myocarditis, necrotizing hepatitis, and DIC (all P < 0.001), with a mortality rate of 54.55% (P < 0.001). Laboratory findings showed more thrombocytopenia, coagulation dysfunction, and organ injury markers in the severe group (all P < 0.001). Mild cases required mainly non-invasive treatment, while severe cases had high mortality despite intensive interventions. Among survivors, 50% required long-term neurological rehabilitation.Conclusion: Severe neonatal EV infection is closely associated with preterm birth and perinatal infection, characterized by thrombocytopenia, coagulation dysfunction, and multiple organ damage. Early monitoring of high-risk neonates, especially preterm infants, should be reinforced. For neonates presenting within the first seven days of life with rash or respiratory distress accompanied by a rapid decline in platelet count, intensive care should be promptly initiated. Further research is needed to explore targeted antiviral therapies and immune modulation strategies.Keywords: neonate, enterovirus, severe infection, symptomatic supportive treatment, retrospective study